Anodes including a conductive layer between an active anode material and a current collector, and electrochemical devices incorporating such anodes
By introducing conductive layers and conductive carbon-based coatings into lithium metal batteries, the problem of limiting the width of lithium foil is solved, and lithium metal batteries with larger sizes and higher energy density are realized, which are suitable for applications with high energy demand such as electric vehicles.
Patent Information
- Application Number
- JP2024544426
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-26
- Filing Date
- 2023-01-25
- Publication Date
- 2025-02-06
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the width of lithium foil of lithium metal secondary batteries is limited to 120mm, resulting in limited size of the manufactured battery and it is difficult to meet the needs of large-capacity batteries, especially in high-energy applications such as electric vehicles.
A conductive layer is introduced between the current collector of the battery and the lithium foil, and a lithium metal battery is manufactured through a continuous roll-to-roll roll process to increase the width of the lithium foil, and a conductive carbon-based coating is used to improve the adhesion between the lithium foil and the current collector, ensuring the stability and conductivity of the battery.
The manufacturing of larger-sized lithium metal batteries has been achieved, which improves the capacity and energy density of the batteries, and is suitable for applications with high energy demands, such as electric vehicles.
Smart Images

Figure 2025503963000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority to U.S. Patent Application No. 17 / 585,120, entitled "Anode Including a Conductive Layer Between an Anode Active Material and a Current Collector, and Electrochemical Device Incorporating Such an Anode," filed on January 26, 2022, which is incorporated herein by reference in its entirety.
[0002] The present disclosure relates generally to the field of electrochemical devices. In particular, the present disclosure relates to an anode including a conductive layer between an anode active material and a current collector, and to an electrochemical device incorporating such an anode. [Background technology]
[0003] Lithium metal batteries, which are rechargeable or secondary batteries, offer higher volumetric and gravimetric energy densities than current lithium-ion batteries. Unlike lithium-ion batteries, which contain an anode (negative electrode) formed from an intercalating material such as graphite, in a typical lithium metal secondary battery, lithium foil (the anode active material) is laminated on both sides of a copper foil (the current collector) to form a conventional lithium-copper-lithium (Li / Cu / Li) anode structure. However, lithium is soft and sticky, and it is difficult to produce ultra-thin (<50 μm thick) lithium foil with widths greater than 120 mm using conventional roll milling processes. This width constraint consequently limits the size of anodes and cells that can be produced using lamination techniques. Summary of the Invention [Problem to be solved by the invention]
[0004] 1A and 1B show a conventional approach to manufacturing a conventional Li / Cu / Li anode (represented by dashed area 10) using a roll-to-roll process 12 that involves sequentially laminating ultra-thin lithium foil ribbons 14A and 14B onto both sides of a copper foil web 16 to form a web-like anode precursor 18. The width Ww of the copper foil web 16 is typically greater than the width Wf of the lithium foil, and the laminated structure typically has bare copper areas 16A along at least one edge of the copper foil web. The bare copper areas 16A are provided to form electrical tabs 10A for enabling electrical contact to the Li / Cu / Li anode 10 punched out of the web-like anode precursor 18 when the Li / Cu / Li anode is assembled into a stacked "jelly roll" of an electrochemical cell. Without the electrical tabs 10A, it would be difficult to connect the multiple layers of Li / Cu / Li anode 10 in the stacked jelly roll to external electrical leads (not shown) in the completed electrochemical cell. As discussed above, the physical properties of lithium limit the width Wf of the lithium foil web 16 to about 120 mm when using the desired ultra-thin lithium foil, which limits the size of Li / Cu / Li anodes, such as the Li / Cu / Li anode 10 of Figures 1A and 1B, that can be fabricated using conventional roll-to-roll lamination techniques, and this limitation severely limits the size of lithium metal electrochemical cells (not shown), such as secondary lithium metal battery cells, that can be fabricated using the ultra-thin lithium metal anodes. As a result, this limitation has hindered the development of lithium metal secondary batteries for applications that require large battery capacity for practical operation, such as electric vehicles. [Means for solving the problem]
[0005] In one embodiment, the disclosure relates to an anode for an electrochemical device, the anode comprising a current collector having a thickness and an active area, the active area having first and second faces across the thickness, a first anode active metal layer secured to the current collector on the first face of the active area, and a first conductive layer comprising polyacrylic acid and positioned between the current collector and the first anode active metal layer and securing the first anode active metal layer to the current collector.
[0006] In another embodiment, the disclosure relates to an anode for an electrochemical device comprising a current collector having a thickness and an active area, the active area having first and second faces across the thickness, a first anode active metal layer secured to the current collector on the first face of the active area, and a first conductive layer located between the current collector and the first anode active metal layer, the first conductive layer comprising a conductive material present in the first conductive layer in an amount ranging from about 50% to about 90% by weight, and a binder binding the conductive material in the first conductive layer, securing the first anode active metal layer to the current collector. [Brief description of the drawings]
[0007] For the purpose of illustrating aspects of the disclosure, the drawings illustrate features and / or characteristics of one or more embodiments of the disclosure, it being understood, however, that the disclosure is not limited to the precise arrangements and instrumentalities shown in the drawings. [Figure 1A] FIG. 2 is a plan view of a portion of a conventional web-like anode precursor in a conventional roll-to-roll lamination process, showing the Li / Cu / Li anode before it is punched from the web-like anode precursor. [Figure 1B] FIG. 1B is an enlarged, exaggerated cross-sectional view of a conventional Li / Cu / Li web-like anode precursor taken along line 1B-1B in FIG. 1A before an anode is punched from the web-like anode precursor. [Diagram 2] FIG. 2 is a flow diagram showing an example of an anode formation lamination method according to the present disclosure. [Figure 3A] 3 is a partial plan view of an exemplary web-like anode precursor that can be made using the method of FIG. 2, and an exemplary anode removed therefrom, the web-like anode precursor shown at different stages of processing, from application of an optional conductive coating patch, to lamination of an anode active material patch, to removal of the anode from the web-like anode precursor. [Figure 3B] 3B is an enlarged, exaggerated cross-sectional view of the exemplary anode of FIG. 3A taken along line 3B-3B of FIG. 3A. [Figure 4] 3 is a high level schematic diagram of an exemplary roll-to-roll lamination process for implementing the exemplary anode formation lamination method of FIG. 2. [Figure 5A] 2A-2C are plan views of portions of different web-like anode precursors showing examples of alternative arrangements of anode regions and anode active material patches (and conductive coating patches, if used) on the web-like anode precursor. [Figure 5B] 2A-2C are plan views of portions of different web-like anode precursors showing examples of alternative arrangements of anode regions and anode active material patches (and conductive coating patches, if used) on the web-like anode precursor. [Figure 5C] 2A-2C are plan views of portions of different web-like anode precursors showing examples of alternative arrangements of anode regions and anode active material patches (and conductive coating patches, if used) on the web-like anode precursor. [Figure 5D] 2A-2C are plan views of portions of different web-like anode precursors showing examples of alternative arrangements of anode regions and anode active material patches (and conductive coating patches, if used) on the web-like anode precursor. [Figure 5E] 2A-2C are plan views of portions of different web-like anode precursors showing examples of alternative arrangements of anode regions and anode active material patches (and conductive coating patches, if used) on the web-like anode precursor. [Figure 6] 1 is a graph of discharge capacity versus cycle life comparing the cycle life performance of an example Li / Cu / Li anode made with a conductive coating layer of the present disclosure and an example Li / Cu / Li anode made without a conductive coating layer. [Figure 7] FIG. 1 is a high level cross-sectional view of an electrochemical cell made using multiple anodes made in accordance with the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] In some aspects, the present disclosure relates to a method for forming an anode for one or more electrochemical devices using a particular lamination technique. Examples of electrochemical devices that can benefit from the anode formation lamination method of the present disclosure include, among others, metal-based secondary batteries and supercapacitors. In this context, "metal-based" means that the electrochemical device in question has one or more anodes each including at least one metal layer that is an anode active material. Examples of metals that can be used for the metal layer include, but are not limited to, lithium, sodium, potassium, magnesium, and aluminum, or alloys containing such metal(s). As described below, in some embodiments, the anode formation lamination method of the present disclosure allows metal anodes, particularly alkali metal anodes such as lithium metal anodes, to be made in larger sizes than conventional laminated anodes made using the same anode active metal. Such larger sizes lead to, for example, higher capacity secondary batteries that overcome the limitations of conventional secondary batteries. As one skilled in the art will readily appreciate, the lamination techniques disclosed herein are cost-effective, and production cost is a particularly important parameter for producing large capacity secondary batteries required for high energy demand applications such as electric vehicles.
[0009] In some aspects, the present disclosure relates to an anode comprising a current collector, a metal anode active layer on one or both sides of the current collector, and a conductive coating (or simply "conductive coating") disposed between the current collector and each metal anode active layer. In some embodiments, the conductive coating is a conductive carbon-based coating, which can include one or more forms of conductive carbon, a binder, and optionally particles of one or more metals. In other embodiments, the conductive coating can include only particles of one or more metals and a binder. In some embodiments, the conductive coating improves the fixation of the alkali metal layer to the current collector. For example, one skilled in the art will understand that in stacked anodes manufactured by conventional methods, a lithium metal layer applied to a copper current collector does not always bond well to the copper current collector and will delaminate from the copper current collector during handling. This delamination can be prevented by using the conductive coating of the present disclosure. The conductive coating of the present disclosure can also function to maintain contact with the lithium metal layer even when most of the lithium metal layer is converted to a porous moss-like structure upon cycling. The conductive coating of the present disclosure may also be used to aid in the positioning of the metal foil sheet of anode active material on the current collector web and / or enable new manufacturing techniques that take advantage of the superior adhesion properties of some embodiments of the conductive coating. Metal-based anodes of the present disclosure that include a conductive coating may be made using any suitable method, such as any one of the anode formation lamination methods disclosed herein, or any suitable conventional method.
[0010] In yet other aspects, the present disclosure relates to methods of making electrochemical devices using any of the methods disclosed herein and / or using any of the conductive coating-containing anodes disclosed herein, and to electrochemical devices made using the methods disclosed herein and / or using any of the conductive coating-containing anodes disclosed herein. The above and other aspects of the present disclosure are described in detail below.
[0011] Before proceeding in more detail, it should be noted that throughout this disclosure, the term "about" when used with a corresponding numerical value refers to ±20% of that numerical value, usually ±10% of that numerical value, often ±5% of that numerical value, and more often ±2% of that numerical value. In some embodiments, the term "about" can also refer to the numerical value itself. It should also be noted that the term "surface" when referring to an anode of the present disclosure, a layer, a coating, a foil, a web, a ribbon, or any other component or region of an anode of the present disclosure, or any other structure or region thereof used to form an anode of the present disclosure, refers to the extent of the component or structure that extends between the edges of the component or structure in a direction perpendicular to the thickness of the component or structure. In other words, in the context of this disclosure, the "surface" of a component or structure is separated by the thickness of the component or structure.
[0012] 2, 3A, 3B, and 4, and correspondingly noting that the first digit of each element number corresponds to the figure in which that element first appears, FIG. 2 illustrates an exemplary anode formation lamination method 200 for forming anodes 300 (only one shown in isolation) for one or more electrochemical devices (not shown), FIGS. 3A and 3B illustrate a web-like anode precursor 304 and an anode 300 made using this method, and FIG. 4 illustrates an exemplary roll-to-roll (R2R) processing system 400 for carrying out various steps of the anode formation lamination method 200. The anode formation lamination method 200 may be used to form multiple anodes 300, which may all be the same size as one another or may have different sizes. Each anode 300 includes a current collector 308 having an active material region 308A and a conductive tab, or simply "tab," 308B formed as an extension of the active material region. Active material region 308A includes anode active material 312 laminated to anode 300 on one or both sides of current collector 308, depending on the requirements of the anode design. Active material region 308A has a length La in a direction parallel to the extension direction Dt of tab 308B from the active material region, which can be any suitable length, such as, for example, from about 50 mm to about 800 mm, from about 100 mm to about 600 mm, or about 100 mm or more, when the thickness Tam of active material 312 is about 50 μm or less, in the range of about 15 μm to about 25 μm, or about 20 μm or less. The width Wa of the active material region 308A in a direction perpendicular to the length La can be any suitable width, such as about 10 mm to about 200 mm, about 20 mm to about 150 mm, or less than about 120 mm, when the thickness Tam is about 50 μm or less, in the range of about 15 μm to about 25 μm, or about 20 μm or less. In some embodiments, the width Wa can be the maximum width of a foil at a given thickness that can be formed from a selected anode active material using conventional foil forming techniques, including widths greater than 200 mm. For example, the maximum width of a lithium foil at present is about 120 mm at a thickness of about 50 μm or less, but future technologies may allow larger widths, which the techniques disclosed herein can readily accommodate.
[0013] The disclosed method allows for the production of lithium anodes, such as lithium-based versions of anode 300, with areal dimensions up to about 150 mm (Wa (FIG. 3A)) by about 600 mm (La (FIG. 3A)) or more, for example, when thickness Tam is about 50 μm or less, particularly as the industry devise methods for producing lithium foils with widths greater than the current practical limit of 120 mm. In one example, while a conventional lamination process resulted in a Li / Cu / Li anode with an areal size of about 53 mm by 45 mm with a lithium thickness of 20 μm, the disclosed lamination method, e.g., lamination method 200 of FIG. 2, resulted in an anode 300 with an active area length La of 550 mm and an active area width of 107 mm with the same lithium thickness (Tam). For secondary batteries assembled using anodes 300 made according to the present disclosure, with or without optional conductive coating patch 328 (see below), the cell capacity (Ah) and energy (Wh) are much higher (e.g., up to 25, 50, or more) in proportion to the anode size. Lithium metal secondary batteries with capacities of 100 Ah or more, required for high energy demand applications such as electric vehicles, can be manufactured using the disclosed methods. As an example comparison, for the same number of stacks, a 53 mm x 45 mm anode will produce a cell with up to about 4 Ah, while a 550 mm x 107 mm anode will produce a cell with up to 100 Ah. Furthermore, the gravimetric energy density (Wh / Kg) and volumetric energy density (Wh / L) of these batteries will also be higher, since larger cells require less packaging. For instance, in the above example, comparing a ~4 Ah cell to a ~100 Ah cell, going from the smaller cell to the larger cell would increase the gravimetric energy density from ~400 Wh / kg to ~410 Wh / kg.
[0014] In some embodiments, the anode 300 may include a conductive coating 316 between the anode active material 312 and the current collector 308 on both sides of the current collector where the anode active material is present. When the conductive coating 316 is present, it is typically desirable for the conductive coating 316 and the anode active material 312 to be approximately coextensive with the active material region 308A, i.e., have approximately the same length Lcc and width Wcc as the length La and width Wa of the corresponding active material region. As shown in FIG. 3A, the anode 300 is shown with the corresponding anode region 320(1) removed from the web-like anode precursor 304. Also shown in FIG. 3A are two additional anode regions 320(2) and 320(3) on the web-like anode precursor 304 that, after being removed therefrom, form two additional anodes (not shown). Each anode region 320(1) through 320(3) includes an active area portion 320A(1) through 320A(3) and a tab portion 320B(1) through 320B(3). In Figure 3A, anode region 320(2) includes an active anode material and is ready for the corresponding anode to be removed, while anode region 320(3) does not yet include an active anode material. Examples of materials for current collector 308, active anode material 312, and conductive coating 316, respectively, are described above and below.
[0015] In block 205, the anode formation lamination method 200 includes providing a current collector web 324. In one embodiment, as shown in FIG. 4, the current collector web 324 may be provided as a ribbon 404 of current collector material suitable for the R2R processing system 400 of FIG. 4. In other embodiments, the current collector web 324 may be provided in another form, such as a sheet form in which the current collector material is provided as individual sheets. The current collector web 324 may be made of any suitable conductive material, such as, for example, a metal such as copper, nickel, titanium, or stainless steel, among others, or any suitable metal alloy. In principle, the type of material used for the current collector web is not limited. The current collector web 324 may have various forms, such as a solid foil, a perforated foil, a woven mesh, or an expanded mesh, among others. In principle, the form of the current collector web 324 is not limited. The percentage of open area to total area in any mesh or other open structure may be in the range of about 5% to about 95%. When a perforated mesh is used, it can be made by a variety of processes, including, but not limited to, conventional punching, rotary die cutting, electroforming, photoetching, and laser cutting. In some embodiments, the current collector web 324 has a width Ww in the range of about 20 mm to about 200 mm, in the range of about 120 mm to about 200 mm, in the range of about 150 mm to about 300 mm, or more, particularly when the thickness Tam of the anode active material is about 50 μm or less and the active material is an alkali metal such as lithium. The length of the current collector web 324 may be any length suitable for carrying out the anode formation lamination method of the present disclosure, such as the anode formation lamination method 200 in a ribbon-based process or a sheet-based process of FIG. 2.
[0016] Tabs 308B of current collector 308 of anode 300 may be formed from uncoated areas 324A of current collector web 304, i.e., areas that are not present with anode active material, or, if optional conductive coating 316 is used, areas of the current collector web that are also not present with conductive coating material. As a result, it is necessary to leave tab portions 320B(1) through 320B(3) of anode region 320 of web-like anode precursor 304 uncoated, as described below.
[0017] In optional block 210, optional conductive coating patches 328 are applied to one or both sides of the current collector web 324, depending, for example, on whether the completed anode 300 will have anode active material on one or both sides of the current collector web. Although only one conductive coating patch 328 is shown in FIG. 3A, in this example, a similar conductive coating patch is also provided on the opposing side of the current collector web 324. If a conductive coating is provided, the conductive coating patch 328 is provided to form interpatch regions 304A, which are uncoated portions of the current collector web 324 where the tab portions 320B of the anode region 320 are / will be located, and where the tabs 308B of the anode 300 are / will be formed. Each interpatch region 304A may have a gap width Wg that is equal to or greater than the length Lt of the corresponding tabs 308B on the respective anode 300. In some embodiments, the gap width Wg may be in the range of about 10 mm to about 30 mm, based on the length Lt of the tabs 308B being of the same or similar dimensions. In other embodiments, the gap width Wg of each interpatch region 304A may be greater than about 30 mm or less than about 10 mm to accommodate a particular anode design.
[0018] When the conductive coating patches 328 are provided on both sides of the current collector web 324, the conductive coating patches for the same anode 300 are aligned with each other so that the conductive coating patches and the inter-patch areas 304A are in the same location as each other along the length of the current collector web 324. In some embodiments, the width Wccp of each conductive coating patch 328 is approximately equal to the width Wa of the active material area 308A of the anode 300 to minimize waste. In some embodiments, the width Wccp of each conductive coating patch 328 is about 1 mm to about 3 mm or more larger than the width Wa of the active material area 308A on both sides of the active material area 308A to ensure that conductive material remains on the cut edges of the anode 300 when the anode 300 is removed from the web-like anode precursor 304.
[0019] In some embodiments, the width Wccp of each conductive coating patch 328 is approximately equal to the width Ww of the current collector web 324, particularly when the anode 300 is fabricated from a single line of the anode region 320 using method 200. In some embodiments, the width Wccp of each conductive coating patch 328 is set to less than about 95% of the width of the current collector web 324 to facilitate waste processing, leaving enough of the current collector web. For example, if the current collector web 324 remains sufficient after removing the anode 300 in an R2R system such as the R2R system 400 of FIG. 4, the waste material can be wound onto a waste collection roll (not shown). In some embodiments, the width Wccp of each conductive coating patch 328 and / or the width Waamp corresponding to the anode active material patch 336 is set to less than 100% of the width Ww of the current collector web 324, such as, for example, about 0.9Ww < Wccp and / or Waamp < Ww, about 0.95Ww < Wccp and / or Waamp < Ww, or about 0.98Ww < Wccp and / or Waamp < Ww. In some embodiments, the length Lccp of each current collector patch 328 is fabricated to be approximately equal to the length La of the active material region 308A of the anode 300 to minimize waste. In some embodiments, the length Lccp of each conductive coating patch 328 is set to be about 1 mm to about 3 mm wider than the length La of the active material region 308A on each side of the active material region 308A, ensuring that conductive material is present at the edge of the cut anode when the anode 300 is removed from the web-like anode precursor 304. Along the edge of the conductive coating patch 328 provided with the tab 308B, the conductive coating is usually in the same plane as the anode active material patch 336 or extends up to about 1 mm beyond the anode active material patch 336. Usually, it is preferred that the conductive coating patch 328 and the anode active material patch 336 do not overlap by more than about 1.5 mm on the tab 308B. Otherwise, the "excess" material may interfere with the tab welding process.
[0020] Each conductive coating patch 328 acts as a primer for the corresponding anode active material patch 336, helping to improve adhesion between the anode active material 312 and the current collector 308 in the final anode 300 while maintaining low contact resistance between them. If provided, each conductive coating patch 328 may be made of any suitable conductive material, such as a conductive carbon material including one or more types of conductive carbon particles and a suitable binder to bind the particles to each other and to the current collector web 324. In other embodiments, the conductive carbon particles may be augmented with metal particles, and in yet other embodiments, only metal particles may be used with a suitable binder.
[0021] When a conductive carbon material is used, it may be provided as a slurry prepared by mixing the conductive carbon with a binder material in an aqueous or organic solvent medium, which is finally dried after being applied to the current collector web 324. The conductive carbon material may be, for example, carbon black, graphite, graphene, carbon fiber, carbon nanotubes, or a mixture thereof. Metals such as powdered silver may also be mixed with the conductive carbon to enhance electrical conductivity. Examples of binder materials include, but are not limited to, PVDF (polyvinylidene fluoride), PVDF-HFP (polyvinylidene fluoride-hexafluoropropylene), CMC (carboxymethylcellulose), SBR (styrene butadiene rubber), PAA (polyacrylic acid), and any mixture thereof.
[0022] As mentioned above, the binder in the conductive coating patch 328 can help the anode active material patch 336 adhere better to the current collector web 324 and prevent delamination of the anode active material from the current collector web and current collector 308 during handling and use. The conductive material in the conductive coating helps maintain low contact resistance between the anode active material 312 and the current collector 308 in the finished anode 300, which, along with better adhesion, helps improve cell cycling performance in secondary batteries fabricated using anodes incorporating such conductive material.
[0023] The thickness of each conductive coating patch 328 may be, for example, in the range of about 0.1 μm to about 5 μm, in the range of about 0.5 μm to about 2 μm, and about 1 μm thick, as well as other ranges and values. In some embodiments, if the surface roughness (Ra, arithmetic mean roughness) of the anode active material is X μm, the thickness of the coating may be in the range of about 0.2X μm to about 2X μm. Current evidence indicates that in some embodiments, including those in which lithium foil is used for the anode active material patch 336, a thickness of about 1 μm for each conductive coating patch 328 may be optimal, based on the following considerations: the conductive coating patch 328 should be substantially sufficient to improve adhesion and conductivity. However, thicker coatings may result in side reactions and add unnecessary weight and volume to the cell. Additionally, there may be a minimum thickness that corresponds to the variation in the average surface roughness of the anode active material (e.g., lithium). This relationship depends on many factors. Thus, it may be directly or inversely proportional. For example, in the case of lithium, lithium metal is easily deformed, and lithium foils with higher roughness may easily adhere to, for example, copper surfaces, and a thin conductive coating may be sufficient. However, while the original lithium surface may bond well to the copper surface, this relationship may be further complicated by any passivation layer present on the surface of the lithium foil, since most lithium foils have a surface passivation layer with different chemical composition and thickness values depending on the specific manufacturing process of each supplier. As a result, the optimal thickness may vary depending on the specific facts involved.
[0024] In some embodiments, the area weight of the conductive coating material in each conductive coating patch 328 is about 0.1 g / m 2 From about 2 g / m 2 and in some embodiments, about 0.5 g / m 2In some embodiments, the surface resistance of each conductive coating patch 328 may be about 30 Ω / sq or less for a coating thickness of about 1 μm, with a surface resistivity of about 3×10 -3 The surface resistivity may be Ω·cm or less. Generally, the unit of surface resistivity is Ω / sq, and the surface resistivity depends on the thickness of each conductive coating patch 328, the thicker the conductive coating patch, the lower the resistance. Thus, for thicknesses other than about 1 μm, the surface resistivity is different from 30 Ω / sq. In some embodiments, the amount of conductive material (e.g., conductive carbon, conductive metal, or combinations thereof) in the conductive coating material may be in the range of about 5% to about 95% by weight, in the range of about 50% to about 90% by weight, in the range of about 60% to about 90% by weight, or in the range of about 70% to about 90% by weight.
[0025] As an example of the benefit of using the conductive coating patch 328, if the anode active material is lithium and the current collector web 324 is copper, fresh lithium typically adheres well to the copper surface. However, a passivation layer that is typically present on the surface of conventional lithium foil inhibits adhesion to the copper. The composition of the passivation layer depends on the atmosphere the lithium foil was originally exposed to during manufacture and is typically made of salts such as lithium carbonate, lithium hydroxide, lithium oxide, and lithium nitride. Additionally, the surface of the lithium foil may also have residual lubricant from the roll mill process used to form the lithium foil. The presence of a passivation layer and / or oil residue on the surface prevents the lithium foil from adhering well to the copper during lamination. Providing the conductive coating patch 328 helps overcome this problem by forming a layer that adheres well to the current collector web 324 and to which the anode active material patch 336 adheres well.
[0026] For example, a peel test was conducted on samples in which lithium foil (anode active material) was pressure-laminated to copper foil (current collector) (one in which the lithium foil was directly attached to the copper foil and one in which a conductive carbon coating was applied between the lithium foil and the copper foil). SCOTCH® tape (available from 3M Corporation, St. Paul, Minnesota) was lightly pressed onto the lithium foil of each sample and slowly peeled off. Although the lamination conditions were the same between the two samples except for the presence of the conductive coating on one sample, the lithium foil laminated directly to the copper foil peeled off from the copper foil together with the tape, whereas the lithium foil laminated to the conductive carbon coating did not peel off with the tape and remained laminated to the conductive carbon coating and the copper foil under the conductive carbon coating. Note that pressure-sensitive tapes other than SCOTCH® tape may be used. If the lithium foil is well attached to the copper foil, the peel force is usually greater than about 200 N / m.
[0027] To apply any conductive coating patch 328 to the current collector web 324, the exemplary R2R system 400 may include a coating applicator 408 suitable for the type of conductive coating material in question. For example, the coating applicator 408 may include one or more coating applicators 408A(1) and 408A(2), such as a knife-type applicator, a spray applicator, or a roller applicator, among others. Exemplary coating processes that may be used include slot die casting, tape casting, gravure, comma, spray coating, and dip coating, among others. There is essentially no limit to the manner in which the conductive coating patch 328 may be applied. The coating applicator 408 may include one or more patterning devices 408B(1) and 408B(2), such as an open mask or silk screen, among others, to ensure that the conductive coating patch is of the desired size. Those skilled in the art will readily understand how to apply any selected conductive coating patches 328 to the current collector web 324 at appropriate locations on the web-like anode precursor 304, and the appropriate coating application apparatus 408 required for such application, and therefore a detailed description of each is not necessary in order for those skilled in the art to practice the present invention to the fullest extent possible without undue experimentation.
[0028] At block 215, the metal foil 332 is laminated to one or both sides of the current collector web 324 as a corresponding anode active material patch 336 (although only one is shown, in this example, another anode active material patch is present opposite the current collector web). Lamination of the metal foil 332 may first include engaging the metal foil 332 with the current collector web 324 with or without the conductive coating patch 328, depending on whether it is used for a particular application. Engagement of the metal foil 332 may be done in any suitable manner, such as, for example, via transfer from a temporary holding substrate or via a pick-and-place process. In some embodiments, the metal foil 332 may be pressed to tightly engage the current collector web 324 and each corresponding conductive coating patch 328, if present. Such pressing may be performed in any suitable manner, such as, for example, using a roller press or a fixed press, among others. In some embodiments, lamination of the metal foil 332 may be performed using a roll mill or a calendering machine, with the lamination pressure being determined by the gap setting between the rolls. In some embodiments, the pressure applied by the roller should not significantly deform the metal foil 332, i.e., there should be a negligible reduction in thickness or increase in width and / or length of the lithium foil. For example, when a conductive coating patch 328 is present, it is typically desirable for the metal foil 332 of the corresponding anode active material patch 336 to remain approximately within the footprint of the underlying conductive coating patch. In some embodiments, it is desirable for the reduction in thickness of the metal foil 332 to be less than about 10% of the original thickness of the metal foil, and for the length and / or width of the metal foil to increase by less than about 2%. Essentially, there is no limit to the manner in which the metal foil 332 can be pressed onto the web-like anode precursor 304.
[0029] The metal foil 332 may have a thickness in the range of about 15 μm to about 25 μm, in some embodiments, about 20 μm, in some embodiments, about 10 μm to about 50 μm, in some embodiments, about 1 μm to about 100 μm, and other ranges and values. These thicknesses are particularly applicable to lithium-containing foils, including pure lithium, alkali metal-based foils in general, and foils based on one or more other metals. Current evidence demonstrates that a thickness of about 20 μm for the metal foil 332, including lithium metal foil, may be an optimal tradeoff of various factors, including cycle life, handling, cost, weight, and plating, while adding to the thickness of an electrochemical cell made using the anode 300. In some embodiments, the thickness of the current collector web 324 may be in the range of about 4 μm to 10 μm, and in some embodiments, about 6 μm, including when the current collector web is a copper foil, among other ranges and values. Current evidence demonstrates that a current collector thickness of 6 μm may be the optimal tradeoff between, for example, weight, strength, energy density, lamination complexity, cost, and thickness.
[0030] In some embodiments, the metal foil 332 may be pre-sized to be approximately equal to the size of the active area portions 320A(1) to 320A(3) of the anode regions 320(1) to 320(3), or the size of the corresponding conductive coating patch 328, or both. Such sizing may be used, for example, in a transfer process from a temporary substrate, or in a pick-and-place process, such as a pick-and-place process using a suitably gentle vacuum. In some embodiments, the metal foil 332 may be provided in a continuous sheet or ribbon. For example, if conductive coating patches 328 are used that provide significant adhesion of the metal foil to the uncoated portions of the current collector web 324, the anode active material patch 336 may be formed by pressing the continuous sheet or ribbon against the current collector web and removing portions of the metal foil 332 from the previously uncoated portions of the current collector web to which the metal foil does not sufficiently adhere. In some embodiments, the width Waamp of each anode active material patch 336 is approximately equal to the width Wa of active material region 308A of anode 300 to minimize waste. In some embodiments, the width Waamp of each anode active material patch 336 is greater than the width Wa of active material region 308A by about 1 mm to about 3 mm on each side of active material region 308A to ensure that conductive material is present at the cut edges of the anode when the anode 300 is removed from the web-like anode precursor 304.
[0031] In some embodiments, if conductive coating patches 328 are used and the conductive coating material used provides suitable properties to the conductive coating patches, method 200 may include, in optional sub-block 215A, aligning the sheet of metal foil 332 with the conductive coating patches using the conductive coating patches. For example, if the conductive coating patches 328 provide a machine-detectable contrast, such as an optical contrast, between the conductive coating patches and the underlying current collector web 324, a suitable detection system may be provided to sense the contrast and provide position information to a control system that controls the alignment of the sheet of metal foil 332 with the conductive coating patches. One example of a detection system is a machine vision system that can detect and locate one or more edges of each conductive coating patch 328.
[0032] 4 and the exemplary R2R system 400, the R2R system can include a lamination area 412 where the metal foil 332 (only some of which are labeled in FIG. 4) engages and is laminated to the current collector web 324. As discussed above, the lamination area 412 can take any of a wide variety of forms depending, for example, on how the metal foil 332 is provided to the current collector web 324, whether a conductive coating patch 328 is used, and how the metal foil is pressed onto the current collector web. In the embodiment shown in FIG. 4, the metal foil 332 is provided as individual foil sheets 416 on a pair of temporary support ribbons 420(1) and 420(2), one on each side of the current collector web ribbon 404, to relatively loosely hold the foil sheet before being laminated to the current collector web ribbon. The illustrated embodiment also includes a roller press 424 that presses the foil sheet 416 into tight engagement with the current collector web ribbon 404 to form the anode active material patch 336.
[0033] In this embodiment, the foil sheet 416 is fed to the current collector web ribbon 404 using, for example, a pair of transfer rollers 428(1) and 428(2) that can apply a relatively small amount of pressure to effect transfer of the foil sheet to the current collector web ribbon. Because there is greater adhesion between the foil sheet 416 and the current collector web ribbon 404, especially when the conductive coating patch 328 is present, than between the foil sheet and the temporary support ribbons 420(1) and 420(2), the temporary support ribbon can be easily peeled away from the anode active material patch 336 that is now part of the web-like anode precursor 304. In some embodiments, the spacing between the foil sheets 416 on the temporary support ribbons 420(1) and 420(2) exactly matches the interpatch area 304A. In other embodiments, the spacing between the foil sheets 416 on the temporary support ribbons 420(1) and 420(2) may not match the interpatch area 304A. In some embodiments, if the spacing between the foil sheets 416 on the temporary support ribbons 420(1) and 420(2) exactly matches the interpatch area 304A, the temporary support ribbons 420(1) and 420(2) and the current collector web ribbon 404 may all be passed through the roller press 424. In this case, the transport rollers 428(1), 428(2) may be omitted.
[0034] 4, when conductive coating patches 328 are used, the exemplary R2R system 400 may optionally include an alignment system 432 that utilizes the conductive coating patches to precisely align the foil sheets 416 with their respective ones of the conductive coating patches. This alignment ensures that each foil sheet 416 is precisely aligned with its corresponding one of the conductive coating patches 336 before the anode active material sheets are firmly laminated by the roller press 424 to form the corresponding anode active material patch 328. When the conductive coating patches 328 include a visually high contrast material, such as a conductive carbon coating, relative to the uncoated material of the current collector web 324, the alignment system 432 may include one or more optical sensors, here two optical sensors 432A(1) and 432A(2), for detecting and aligning at least one edge of each conductive coating patch. Alignment system 432 may include one or more controllers 432B (only one shown) and one or more actuators, such as stepper motors (not shown), that the controllers control to precisely advance each of temporary support ribbons 420(1) and 420(2). Controller 432B may be programmed to use one or more edge position information from optical sensors 432A(1) and 432A(2) and position information of temporary support ribbons 420(1) and 420(2) to precisely control alignment of foil sheet 416 with corresponding ones of conductive coating patches 324. One of ordinary skill in the art will understand how to implement various types of alignment systems that can use conductive coating patches 328 to aid in aligning foil sheet 416 with conductive coating patches 328 without undue experimentation.
[0035] The exemplary method 200 further includes block 220 of forming an anode 300 from the web-like anode precursor 304. The anode may be formed from the web-like anode precursor 304 in any suitable manner, such as by punching, shearing, or otherwise cutting the web-like anode precursor 304 at anode regions, e.g., anode regions 320(1) to 320(3), to form and cut the resulting anode 300 therefrom. In this regard, FIG. 4 illustrates the exemplary R2R system 400 as including an anode forming apparatus 436, which may include any suitable automated punch, shear, or other cutting device(s) that may be configured to form one or more anodes 300 at a time. Those skilled in the art will readily understand how to implement a suitable anode forming apparatus 436 without undue experimentation. The formed anode 300 may be ready for use in a next step in fabricating one or more electrochemical devices (not shown) using the anode 300 so formed.
[0036] 5A-5E show several exemplary alternative arrangements of the anode region and anode active material patch (and underlying conductive coating patch, if present) on various web-like anode precursors that can be used in place of the arrangement of the anode region 320 and anode active material patch 336 (and conductive coating patch 328, if present) on the web-like anode precursor 304 of FIG. 3A. It should be noted that the alternative arrangements shown for the web-like anode precursor 304 of FIG. 3A are not limited to the alternative arrangements of FIGS. 5A-5E, but rather, these are exemplary arrangements provided to illustrate the flexibility of the method of forming an anode according to the present disclosure. In the following description of FIGS. 5A-5E, no reference is made to conductive coating patches for ease of explanation. However, as noted above, conductive coating patches may actually be present under the corresponding anode active material patch, for example, in the manner described above in connection with FIGS. 2-4. It should also be noted that the alternative arrangements of FIGS. 5A-5E are described as if the anode active material patch were disposed only on the surface of the web-like anode precursor, as shown in the figures. However, the back side of the web-like anode precursor may likewise have anode active material patches (and optional conductive coating patches) that match the anode active material patches on the front side of the web-like anode precursor. It is further noted that in all respects other than the different arrangement of the anode regions and anode active material patches, such as materials, thickness, area, and fabrication process, the anode regions of Figures 5A-5E may be the same as or similar to the anode regions described elsewhere in this disclosure, such as anode regions 320(1)-320(3) of Figure 3A.
[0037] 5A shows an example of a web-like anode precursor 500 in which anode active material patches 504(1) through 504(5) (solid lines) are provided in a single line on an underlying current collector web 508. In this example, each anode active material patch 504(1) through 504(5) is provided to form a single anode region 512(1) through 512(5) (dashed lines) that will eventually be removed from the web-like anode precursor 500 to form a corresponding anode (not shown, similar to anode 300 in FIGS. 3A and 3B ).
[0038] As can be seen by comparing Figure 5A with Figure 3A, the difference between the web-like anode precursor 500 of Figure 5A and the web-like anode precursor 304 of Figure 3A is that immediately adjacent pairs of tab portions 512A (here, 512A(2) to 512A(5)) of anode regions 512(2) to 512(5) are disposed in the same interpatch region 516 (here, 516(1) and 516(2)). The interpatch region 520 (here, 520(1) and 520(2)) can be smaller than the interpatch region 516 that includes the pair of tab portions 512A(2) to 512A(5), thereby reducing waste of current collector web 508.
[0039] FIG 5B is generally similar to FIG 5A, but in FIG 5B the feature of minimizing the size of the interpatch regions 520 (FIG 5A) has been pursued to the extreme, such that these interpatch regions have been eliminated altogether. In this manner, each pair of anode active material patches 504(1) through 504(4) opposite an interpatch region 520 (FIG 5A) in FIG 5A is substantially combined into one anode active material patch 524 in FIG 5B, in this example, anode active material patches 524(1) and 524(2) are approximately twice as large as anode active material patches 504(1) through 504(5) in FIG 5A, respectively. In this configuration, each anode active material patch 524 in FIG 5B is provided to form two anode regions 528. Here, anode active material patch 524(1) is formed with anode regions 528(1) and 528(2), and anode active material patch 524(2) is formed with anode regions 528(3) and 528(4). If the processing capacity of the anode active material used is a constraint on the amount of anode area required, the configuration of FIG. 5B may not be feasible. For example, if the anode active material is lithium, processing capacity limitations may limit the length of the anode active material patches 504 and 524 shown in FIGS. 5A and 5B. In such cases, it may be necessary to use a different configuration that provides a one-to-one correspondence between the number of anode active material patches and the anode regions created therefrom, including, for example, those shown in FIGS. 3A and 5A.
[0040] Figures 5C through 5E show multi-line variations 530, 550, and 570 of the exemplary configurations shown in Figures 3A, 5A, and 5B, respectively. In considering the multi-line variations 530, 550, and 570 of Figures 5C through 5E, the reader may refer to Figures 3A, 5A, and 5B and the corresponding description for information regarding the corresponding single-line configurations, as these multi-line variations may be made by starting with larger (e.g., wider) current collector webs 534, 554, and 574, respectively, and repeating the corresponding single-line configurations multiple times on such larger current collector webs. 5C-5E show two lines 538(1) and 538(2), 558(1) and 558(2), 578(1) and 578(2) of anode active material patches 542 (here, 542(1) through 542(6)), 562 (here, 562(1) through 562(10)), and 582 (here, 582(1) and 582(4)), respectively, although it should be noted that in other embodiments, more lines may be provided. In general, the only limitation on the number of lines 538, 558, and 578 implemented is the availability of sufficiently large current collector webs 534, 554, and 574, as well as the ability to fabricate the corresponding manufacturing equipment. Also, as with other embodiments disclosed herein, it should be noted that each of the current collector webs 534, 554, and 574 may be, for example, sheet-type or ribbon-type, depending on the type of processing equipment used. For example, ribbon-type current collector webs are readily adapted for R2R processing, such as R2R system 400 of FIG.
[0041] It should be noted that in all of the embodiments shown in Figures 3A through 5E, all anode regions, and the corresponding anode active material patches, any conductive coating patches, if present, and the anodes formed therefrom, are uniform in size in each figure. However, while this may be typical in the manufacturing process of commonly sized electrochemical cells, this need not necessarily be the case. For example, some embodiments of the anode formation methods of the present disclosure may be tailored to produce anodes of different sizes on the same web-like anode precursor.
[0042] FIG. 6 is a graph comparing cell cycle life performance, in terms of discharge capacity versus cycle number, using a lithium-copper (Li / Cu) anode (20 μm thick lithium, 8 μm thick copper applied to both sides, 1 μm thick coating, which is comprised of about 70% to about 90% carbon black and PVDF) with and without the conductive coating of the present disclosure. To generate the data for this graph, cycle life tests were performed on a multi-layer pouch cell comprised of a nickel-manganese-cobalt (NMC) oxide based cathode and a porous polyolefin based separator. The pores in the cathode and separator are filled with Li + Filled with a conductive electrolyte, which typically contains a lithium salt such as LiPF6 or LiFSI dissolved in a carbonate or ethereal solvent, the cells were cycled at charge / discharge rates of C / 5 to 1C between 2.5 V and 4.3 V.
[0043] As shown in FIG. 6, the inclusion of the conductive coating of the present disclosure on the copper current collector was found to improve the cycle life performance of cells with lithium anodes. As the number of cycles increased, the dense lithium gradually became more porous, and the conductive coating helped to maintain good electrical contact between the porous lithium and the copper current collector substrate. This resulted in a more uniform current density distribution and uniform lithium plating / stripping, which further improved the cycle life performance. The initial area specific impedance (ASI) of cells made using copper current collectors with a conductive coating on them was higher (about 38 Ω·cm for the coated) compared to cells with uncoated copper current collectors. 2 whereas the uncoated one is about 28 Ω cm 2 ), but the difference gradually decreased as the number of cycles of the cells increased, and after 500 cycles, the relative ASI of the cells fabricated with conductively coated copper current collectors was found to be lower compared to the cells with uncoated copper current collectors (the coated ones were approximately 85 Ω cm 2 whereas the uncoated one is about 92 Ω cm 2 ).
[0044] It should be noted that if a conductive coating of the present disclosure, such as optional conductive coating 316 of exemplary anode 300 of Figure 3A, is present in the anode, the anode need not be fabricated using the layering methods of the present disclosure. For example, an anode active material equivalent to anode active material 312 of anode 300 may be applied using other methods, such as vapor deposition, among other potential techniques that are or may be developed.
[0045] FIG. 7 illustrates an exemplary secondary battery 700 made according to the present disclosure. In particular, the exemplary battery 700 includes a stacked jelly roll 704 including multiple anodes 708 that include a conductive coating (not shown) of the present disclosure, such as the conductive coating 316 of FIG. 3A, and / or are made using a lamination method of the present disclosure, such as the lamination method 200 of FIG. 2. The novelty of the exemplary secondary battery 700 may result from an inherent conductive coating layer (not shown, but see, for example, the conductive coating 316 of FIG. 3A and FIG. 3B) included on the anode 708 itself, and / or its area being larger than that of conventionally produced stacked anodes, as well as the improved cycle life performance and / or higher gravimetric and volumetric energy density obtained compared to anodes of conventional construction and manufacturing methods. The stacked jelly roll 704 also includes multiple separator layers 716 and multiple cathodes 720 electrically isolated from the anodes 708 by the separator layers.
[0046] In this example, the stacked jelly roll 704 is enclosed in a casing, here a pouch-type casing 712, along with a suitable electrolyte (not shown, but present in at least a separator layer 716 (not all are shown) and can be considered part of the polymer electrolyte if a solid or gel electrolyte is used). In other embodiments, the pouch-type casing 712 may be replaced with a different type of casing, such as a rigid-walled enclosure, among others. Essentially, the type of casing is only important to the extent that it provides the necessary functionality, including providing an enclosed volume to house the stacked jelly roll 704 and the electrolyte. Those of skill in the art are familiar with the techniques and materials for constructing the pouch-type casing 712 or other types of casings that a particular design may include. Thus, further details regarding the casing 712 are not necessary herein for those of skill in the art to embody the secondary battery 700 without undue experimentation.
[0047] As discussed above, each anode 708, similar to the exemplary anode 300 described above, can include any suitable anode active metal, such as lithium, sodium, potassium, magnesium, or aluminum, or any suitable combination thereof. Depending on the type of battery, each cathode includes a suitable cathode active material, such as, for example, lithium-metal, sodium-metal, lithium-air, lithium-sulfur, etc. In one or more embodiments, the cathode includes Li x M y O z where M is a transition metal such as Co, Mn, Ni, V, Fe, or Cr.
[0048] In one or more embodiments, each cathode 720 comprises LiCoO2, Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2, Li(Ni 0.8 Co 0.15 Al 0.05 )O2, LiMn2O4, Li(Mn 1.5 Ni 0.5 In one or more embodiments, each cathode 720 may comprise a layered or spinel oxide material selected from the group including Li x M y PO zwhere M is a transition metal element such as Co, Mn, Ni, V, Fe, or Cr. In one or more embodiments, each cathode 720 may be a phosphate material selected from the group including LiFePO4, LiNiPO4, LiCoPO4, or LiMnPO4. In one or more embodiments, each cathode 720 may include a porous coating including a cathode active material powder, a polymeric binder such as PVDF, and a conductive diluent such as carbon black. In one or more embodiments, each cathode 720 may comprise a porous coating on an aluminum foil. In one or more embodiments, each cathode 720 may include lithium cobalt oxide (or lithium cobalt oxide), lithium manganese oxide (also known as spinel or lithium manganese oxide), lithium iron phosphate, and lithium nickel manganese cobalt (or NMC) and / or lithium nickel cobalt aluminum oxide (or NCA). In one or more embodiments, each cathode 720 may include nano-sized and nano-structured sulfur-based composites such as sulfur-impregnated core-shell hierarchical porous carbon (HPC) composites, sulfur / graphene nanosheet (GNS) composites, sulfur@rGO (reduced graphene oxide) composites with sucrose-like structures, and CS@PANi (polyaniline) composites with polymeric globular network structures, among others. In one or more embodiments, each cathode 720 may include a carbon layer sandwiched around a current collector, or may include a carbon layer covered with a polymer film, such as a PTFE film. The carbon layer may include a metal catalyst that enhances the oxygen reduction rate and increases the specific capacity of the cathode 720. Examples of metal catalysts include, but are not limited to, manganese, cobalt, ruthenium, platinum, silver, and mixtures thereof.
[0049] In one or more embodiments, when the electrolyte is a liquid, each separator layer 716 may be made from any one or more materials, at least one of which is a dielectric. For example, in one or more embodiments, each separator layer 716 may be made from polypropylene or polyethylene, or any suitable combination thereof (e.g., blends, layers, coatings, etc.). One of ordinary skill in the art will appreciate the various materials and structures that can be used to make each separator layer 716.
[0050] With regard to the electrolyte, in one example, the secondary battery 700 is a lithium metal battery, meaning that the anode 708 comprises lithium metal, and lithium ions are deposited and stripped off during charge and discharge cycles, respectively. Correspondingly, the electrolyte contains lithium ions (not shown) that flow between the anode and the cathode 720 in the stacked jelly roll 704 during charge and discharge cycles. As a result, in this example, the electrolyte includes one or more lithium-based salts in a suitable form, such as a solution, eutectic mixture, or molten form, among others. In some embodiments, the electrolyte may contain one or more solvents, one or more performance and / or property enhancing additives, and / or one or more polymers, among others. The electrolyte may be in any suitable state of matter, such as a liquid, gel, or solid state. The composition of the electrolyte, whether a lithium metal-based version of the secondary battery 700 or a version based on other types of metals (e.g., sodium, potassium, aluminum, magnesium, etc.), may be any composition suitable for the particular application at issue, and may be determined by the designer of the particular embodiment of the secondary battery.
[0051] Examples of salts that can be used in the electrolyte include, but are not limited to, LiFSI, LiTFSI, and lithium fluorosulfonyl(trifluoromethylsulfonyl)imide (LiFTFSI), LiPF6, LiAsF6, LiBF4, LiBOB, Li-triflate, and any combination thereof. In one or more embodiments, for example, the first salt X1 +Y1 - And 2x salt + Y2 - Two or more salts can be combined as a eutectic mixture, such as a eutectic mixture comprising a first salt X1+ and a second salt X2+. + are different alkali metal cations, and Y1 - and Y2 - are different sulfonimide anions. In one or more embodiments, Y - and Y2 - is FSO2N-SO2F(FSI - ) and FSO2N-SO2CF3(FTFSI - ) and / or X1 + and X2 + Li + , Na + , K + , R b + , and Cs + In one or more embodiments, the eutectic mixture may be selected from the group consisting of a third salt X3 + Y3 - X3 + is X1 + and X2 + In one or more embodiments, Y1 - , Y2 - , and Y3 - is FSO2N-SO2F(FSI - ) and FSO2N-SO2CF3(FTFSI - ) and / or X1 + , X2 + , and X3 + Li + , Na + , K + , Rb + , and Cs + may be selected from the group consisting of:
[0052] In one or more embodiments, the electrolyte may include an imide salt, such as lithium bisfluorosulfonylimide (LiN(FSO2)2) in an aprotic solvent, and a perchlorate salt. Other lithium imide salts having a fluorosulfonyl (FSO2) group, such as LiN(FSO2)2, LiN(FSO2)(CF3SO2), LiN(FSO2)(C2F5SO2), may be used in place of or in any combination with lithium bisfluorosulfonylimide (LiN(FSO2)2). In one or more embodiments, the perchlorate salt may include LiClO4. In one or more embodiments, the perchlorate salt has a concentration of 0.05M moles / liter to 0.50M moles / liter of the organic solvent. In one or more embodiments, the perchlorate salt is selected from the group consisting of LiClO4, Ca(ClO4)2, Sr(ClO4)2, Mg(ClO4)2, Ba(ClO4)2, and any combination or mixture thereof.
[0053] The electrolyte has the formula R1-(O-CH2-CH2) nThe electrolyte may include a glyme of the formula -O-R2, where n=1-4, and at least one of R1 and R2 is a hydrocarbon side chain having at least two carbon atoms. In one or more embodiments, such electrolytes may further include a diluent selected from the group consisting of fluorinated glymes and fluorinated ethers. The fluorinated diluent allows for the use of more stable glyme-based solvents with longer side chains, such as DEE (1,2-diethoxyethane or ethylene glycol diethyl ether), DPE (1,2-dipropoxyethane or ethylene glycol dipropyl ether), DBE (1,2-dibutoxyethane or ethylene glycol dibutyl ether), diethylene glycol diethyl ether, diethylene glycol dipropyl ether, diethylene glycol dibutyl ether, triethylene glycol diethyl ether, triethylene glycol dipropyl ether, triethylene glycol dibutyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol dipropyl ether, tetraethylene glycol dibutyl ether, etc. In one or more embodiments, the diluent may be the fluorinated ether 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), or the fluorinated ether bis(2,2,2-trifluoroethyl) ether (BTFE). In one or more embodiments, the diluent may include a suitable hydrocarbon molecule having at least one oxygen (-O-) bond and at least one fluorine (-F) substitution. In a specific example, DEE and TFE are combined with each other. In one or more embodiments, the solvent:diluent ratio of the electrolyte made according to this paragraph may be in the range of about 10:90 to 100:0. In one or more embodiments, the solvent:diluent ratio may be desired to be in the range of about 40:60 to about 90:10, and in one or more embodiments, the solvent:diluent ratio may be desired to be in the range of about 60:40 to about 80:20.
[0054] In one or more embodiments, the electrolyte may be a solvent-free liquid lithium sulfonimide salt composition consisting essentially of an adduct of a molecule of lithium sulfonimide salt with a molecule of at least one anhydrous ethereal solvent. In such embodiment(s), examples of lithium sulfonimide salt compositions that can be used for the anhydrous lithium sulfonimide salt include, but are not limited to, LiFSI, LiTFSI, and LiFTFSI, and examples of anhydrous ethereal solvents that can be used for the one or more anhydrous ethereal solvents include, but are not limited to, dimethoxyethane, ethoxymethoxyethane, diethoxyethane, dimethoxymethane, diethoxymethane, ethoxymethoxymethane, dioxane, and crown ethers. In general, any ethereal solvent can be used. In such embodiment(s), substantially all of the molecules of the at least one ethereal solvent are coordinated with a molecule of at least one lithium sulfonimide salt. In one or more embodiments, the at least one ethereal solvent is present in the solvent-free lithium sulfonimide salt composition in an amount less than 5% by weight of the solvent-free lithium sulfonimide salt composition.
[0055] In one or more embodiments, the electrolyte includes an organic solvent such as a cyclic carbonate, such as ethylene carbonate or propylene carbonate, and derivatives thereof. In one or more embodiments, the electrolyte includes a linear carbonate, such as dimethyl carbonate, diethyl carbonate, or ethyl methyl carbonate. In one or more embodiments, the electrolyte includes an organic solvent such as a cyclic ether, such as tetrahydrofuran or tetrahydropyran, and derivatives thereof. In one or more embodiments, the electrolyte includes an organic solvent such as a glyme, such as methoxyethane, diethoxyethane, triglyme, or tetraglyme, and derivatives thereof. In one or more embodiments, the electrolyte includes an organic solvent such as an ether, such as diethyl ether, or methyl butyl ether, and derivatives thereof. In one or more embodiments, the electrolyte includes an organic solvent such as a sulfonyl solvent, such as N,N-dialkylsulfamoyl fluoride, and derivatives thereof, and combinations thereof. In one or more embodiments, the electrolyte includes a mixture of the same organic solvent or a mixture of two or more organic solvents.
[0056] In one or more embodiments, the electrolyte may include one or more inorganic electrolytes selected from the group consisting of lithium silicate, lithium borate, lithium aluminate, lithium phosphate, lithium oxynitride, lithium oxyboride, lithium silicate sulfide, lithium borosulfide, lithium aluminosulfide, lithium phosphosulfide, and any combination thereof. In one or more embodiments, the electrolyte may include Al-doped LLZO(Li 6.25 Al 0.25 La3Zr2O 12 ) Garnet oxide, Perovskite (Li 0.29 La 0.57 TiO3), LISICON (Li 14 ZnGeO 16 ), NASICION (Li 1.3 Al 0.3 Ti 1.7 (PO4)3), thio-LISICON(Li 10 GeP2S12 ), or other glass (LiPON) or glass-ceramic (70Li2S·30P2S5) based materials, or mixtures thereof. In one or more embodiments, the electrolyte may include a solid or gel based polymer electrolyte having PEO (polyethylene oxide), PPO (polypropylene oxide), PAN (polyacrylonitrile), PMMA (polymethyl methacrylate), PVC (polyvinyl chloride), PVDF (polyvinylidene fluoride), PVDF-HFP (polyvinylidene fluoride-hexafluoropropylene), (polyacrylic acid), or any mixtures thereof.
[0057] Although the above examples of electrolytes are primarily based on lithium-based salts, those skilled in the art will appreciate that the lithium-based salts may be substituted with suitable non-lithium-based salts.
[0058] Generally, the electrolytes of the present disclosure may have a salt concentration in the range of about 0.1 M to about 10 M, while in some embodiments the salt concentration is preferably in the range of about 1 M to about 5 M, and in other embodiments the salt concentration is preferably in the range of about 2 M to about 3 M.
[0059] The exemplary secondary battery 700 also includes a positive terminal 724 electrically connected to each of the cathodes 720 via corresponding electrodes 728(1) through 728(5). Similarly, the lithium metal battery further includes a negative terminal 732 electrically connected to tab 708A of anode 708 via corresponding electrodes 736(1) through 736(4).
[0060] Various modifications and additions can be made without departing from the spirit and scope of the present disclosure. Each feature of the various embodiments described above may be combined with features of other described embodiments, as necessary, to provide multiple feature combinations in related new embodiments. Moreover, although several separate embodiments have been described above, what has been described herein is merely illustrative of the application of the principles of the present invention. Furthermore, although certain methods herein may be illustrated and / or described as being performed in a particular order, the order is highly variable within the scope of one of ordinary skill in the art to achieve aspects of the present disclosure. Thus, the present specification is meant to be interpreted only as an illustrative method, and not as limiting the scope of the present invention.
[0061] In some embodiments, the disclosure relates to an anode for an electrochemical device comprising a current collector having a thickness and an active area, the active area having first and second faces across the thickness, a first metal foil secured to the current collector on the first face of the active area, and a first conductive layer located between the current collector and the first metal foil and securing the first metal foil to the current collector.
[0062] In one or more embodiments of the anode, the first conductive layer comprises a conductive carbon layer.
[0063] In one or more embodiments of the anode, the conductive carbon layer consists essentially of conductive carbon particles and a binder.
[0064] In one or more embodiments of the anode, the conductive carbon particles are present in an amount of about 50% to about 90%, about 60% to about 90%, or about 70% to about 90% by weight of the conductive carbon layer.
[0065] In one or more embodiments of the anode, the conductive layer has a thickness in the range of about 0.1 μm to about 5 μm.
[0066] In one or more embodiments of the anode, the conductive layer has a thickness in the range of about 0.5 μm to about 2 μm.
[0067] In one or more embodiments of the anode, the conductive layer has a thickness of about 1 μm.
[0068] In one or more embodiments of the anode, the conductive layer has a thickness of about 0.1 g / m 2 From about 2 g / m 2 is present with an areal weight of
[0069] In one or more embodiments of the anode, the current collector comprises copper and the first metal foil comprises lithium.
[0070] In one or more embodiments of the anode, the current collector has a thickness in the range of about 4 μm to about 10 μm, and the first metal foil has a thickness in the range of about 15 μm to about 25 μm.
[0071] In one or more embodiments of the anode, the anode includes a second metal foil secured to the current collector on the second side of the active area, and a second conductive layer located between the current collector and the second metal foil and securing the second metal foil to the current collector.
[0072] In some embodiments, the present disclosure relates to an electrochemical device comprising a cathode, an electrolyte, and an anode, any one of the anodes described herein.
[0073] Exemplary embodiments have been disclosed above and are illustrated in the accompanying drawings. Those skilled in the art will appreciate that various modifications, omissions and additions may be made to what is specifically disclosed herein without departing from the spirit and scope of the present disclosure.
Claims
1. a current collector having a thickness and an active area, the active area having first and second faces opposed across the thickness; a first anode active metal layer secured to the current collector on the first side of the active region; a first conductive layer comprising polyacrylic acid and located between the current collector and the first anode active metal layer, the first conductive layer securing the first anode active metal layer to the current collector; 1. An anode for an electrochemical device comprising:
2. The anode of claim 1 , wherein the first conductive layer further comprises conductive particles.
3. The anode of claim 2 , wherein the conductive particles comprise conductive carbon particles.
4. The anode of claim 3 , wherein the conductive particles further comprise conductive metal particles.
5. The anode of claim 2 , wherein the conductive particles comprise conductive metal particles.
6. 3. The anode of claim 2, wherein the polyacrylic acid binds the conductive particles within the first conductive layer.
7. 3. The anode of claim 2, wherein the conductive particles are present in an amount of about 50% to about 90% by weight of the first conductive layer.
8. 3. The anode of claim 2, wherein the conductive particles are present in an amount of about 60% to about 90% by weight of the first conductive layer.
9. 10. The anode of claim 1, wherein the first anode active metal layer comprises a first metal foil and the first conductive layer secures the first metal foil to the current collector.
10. 2. The anode of claim 1, wherein said first conductive layer consists essentially of conductive particles and a binder comprising said polyacrylic acid that binds said conductive particles in said first conductive layer.
11. 11. The anode of claim 10, wherein the binder comprises polyacrylic acid.
12. 11. The anode of claim 10, wherein the binder further comprises a material selected from the group consisting of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, carboxymethyl cellulose, styrene-butadiene rubber, and mixtures thereof.
13. 10. The anode of claim 1, wherein the conductive layer has a thickness in the range of about 0.1 μm to about 5 μm.
14. 10. The anode of claim 1, wherein the first conductive layer has a thickness in the range of about 0.5 μm to about 2 μm.
15. The anode of claim 1 , wherein the first conductive layer has a thickness of about 1 μm.
16. The first conductive layer has a thickness of about 0.1 g / m 2 to about 2 g / m 2 13. The anode of claim 1, wherein the anode is present at an areal weight of
17. 10. The anode of claim 1, wherein the current collector comprises copper and the first anode active metal layer comprises lithium.
18. the current collector has a thickness in the range of about 4 μm to about 10 μm; 20. The anode of claim 17, wherein the first metal foil has a thickness in the range of about 15 μm to about 25 μm.
19. 20. The anode of claim 17, wherein said first conductive layer consists essentially of conductive carbon particles and a binder comprising said polyacrylic acid that binds said conductive carbon particles together in said first conductive layer.
20. 20. The anode of claim 19, wherein the conductive carbon particles are present in an amount of about 50% to about 90% by weight of the conductive carbon layer.
21. 20. The anode of claim 17, wherein the first conductive layer has a thickness in the range of about 0.1 μm to about 5 μm.
22. 20. The anode of claim 17, wherein the first conductive layer has a thickness in the range of about 0.5 μm to about 2 μm.
23. 20. The anode of claim 17, wherein the first conductive layer has a thickness of about 1 μm.
24. The first conductive layer has a thickness of about 0.1 g / m 2 to about 2 g / m 2 20. The anode of claim 17, wherein the anode is present at an areal weight of
25. a second anode active metal layer secured to the current collector on the second side of the active region; a second conductive layer located between the current collector and the second anode active metal layer, the second conductive layer securing the second anode active metal layer to the current collector; 10. The anode of claim 1 further comprising:
26. 26. The anode of claim 25, wherein the second anode active metal layer comprises a second metal foil.
27. 26. The anode of claim 25, wherein the second conductive layer is identical to the first conductive layer of any one of claims 1 to 23.
28. 10. The anode of claim 1, wherein the first anode active metal layer comprises a lithium foil having a width of at least 20 mm and a length of at least 120 mm.
29. 30. The anode of claim 28, wherein the current collector comprises copper.
30. 10. The anode of claim 1, wherein the current collector comprises a solid metal foil.
31. 10. The anode of claim 1, wherein the current collector comprises a perforated metal foil.
32. 10. The anode of claim 1, wherein the current collector comprises a metal mesh.
33. 10. The anode of claim 1, wherein the current collector has a thickness in the range of about 4 μm to about 10 μm.
34. 34. An electrochemical device comprising a cathode, an electrolyte, and an anode according to any one of claims 1 to 33.
35. a current collector having a thickness and an active area, the active area having first and second faces opposed across the thickness; a first anode active metal layer secured to the current collector on the first side of the active region; a first conductive layer located between the current collector and the first anode active metal layer, the first conductive layer comprising a conductive material present in the first conductive layer in an amount ranging from about 50% to about 90% by weight and a binder that binds the conductive material in the first conductive layer, the first conductive layer securing the first anode active metal layer to the current collector; 1. An anode for an electrochemical device comprising:
36. 36. The anode of claim 35, wherein the conductive material is present in the first conductive layer in an amount in the range of about 60% to about 90% by weight.
37. 36. The anode of claim 35, wherein the conductive material comprises conductive particles.
38. 40. The anode of claim 37, wherein the conductive particles comprise conductive carbon particles.
39. 40. The anode of claim 38, wherein the conductive particles further comprise conductive metal particles.
40. 38. The anode of claim 37, wherein the conductive particles comprise conductive metal particles.
41. 36. The anode of claim 35, wherein the binder is selected from the group consisting of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, and mixtures thereof.
42. 42. The anode of claim 41, wherein the binder comprises the polyacrylic acid.
43. 36. The anode of claim 35, wherein the first anode active metal layer comprises a first metal foil and the first conductive layer secures the first metal foil to the current collector.
44. 36. The anode of claim 35, wherein the conductive layer has a thickness in the range of about 0.1 μm to about 5 μm.
45. 36. The anode of claim 35, wherein the first conductive layer has a thickness within a range of about 0.5 μm to about 2 μm.
46. 36. The anode of claim 35, wherein the first conductive layer has a thickness of about 1 μm.
47. The first conductive layer has a thickness of about 0.1 g / m 2 to about 2 g / m 2 36. The anode of claim 35, wherein the anode is present at an areal weight of
48. 36. The anode of claim 35, wherein the current collector comprises copper and the first anode active metal layer comprises lithium.
49. 49. The anode of claim 48, wherein the current collector has a thickness in the range of about 4 μm to about 10 μm and the first metal foil has a thickness in the range of about 15 μm to about 25 μm.
50. 50. The anode of claim 48, wherein the first conductive layer consists essentially of conductive carbon particles and a binder comprising polyacrylic acid that binds the conductive carbon particles together in the first conductive layer.
51. 49. The anode of claim 48, wherein the first conductive layer has a thickness within the range of about 0.1 μm to about 5 μm.
52. 49. The anode of claim 48, wherein the first conductive layer has a thickness within a range of about 0.5 μm to about 2 μm.
53. 49. The anode of claim 48, wherein the first conductive layer has a thickness of about 1 μm.
54. The first conductive layer has a thickness of about 0.1 g / m 2 to about 2 g / m 2 49. The anode of claim 48, wherein the anode is present at an areal weight of
55. a second anode active metal layer secured to the current collector on the second side of the active region; a second conductive layer located between the current collector and the second anode active metal layer, the second conductive layer securing the second anode active metal layer to the current collector; 36. The anode of claim 35 further comprising:
56. 56. The anode of claim 55, wherein the second anode active metal layer comprises a second metal foil.
57. 56. The anode of claim 55, wherein the second conductive layer is the same as the first conductive layer of any one of claims 1 to 23.
58. 36. The anode of claim 35, wherein the first anode active metal layer comprises a lithium foil having a width of at least 20 mm and a length of at least 120 mm.
59. 60. The anode of claim 58, wherein the current collector comprises copper.
60. 36. The anode of claim 35, wherein the current collector comprises a solid metal foil.
61. 36. The anode of claim 35, wherein the current collector comprises a perforated metal foil.
62. 36. The anode of claim 35, wherein the current collector comprises a metal mesh.
63. 36. The anode of claim 35, wherein the current collector has a thickness in the range of about 4 μm to about 10 μm.
64. A cathode, an electrolyte, and an anode according to any one of claims 35 to 63.
13. An electrochemical device comprising:
Citation Information
Patent Citations
Manufacturing method of negative electrode for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery using it
JP2007280926A
Polar plate, electrode body, and power storage element
JP2019102185A
Methods of preparing lithium metal anodes
US20190319259A1
Negative electrode for lithium metal battery, manufacturing method of the same, and lithium metal battery including the same
US20200259163A1
Negative electrode for lithium secondary battery and manufacturing method thereof
US20200403230A1